1993
DOI: 10.1007/bf00016293
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lead availability in soils contaminated by mine spoil

Abstract: The uptake of lead by two contrasting plant species, radish and red rescue, grown in soils contaminated by mine spoil was investigated. Uptake was found to be poorly correlated either with pH or total Pb concentration in the soils. By contrast, a good correlation was obtained, particularly for red fescue, between Pb uptake and Pb concentration in the solution of equilibrated soil suspensions over a wide range of soil pH, total soil Pb and soil solution Pb concentration.Calculations suggested a similar order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Their presence has implications for environmental health due to potential uptake by plants (Harding and Witton 1981;Jopony and Young 1993) and animals (Abrahams and Steigmajer 2003) and creates the possibility for the remobilization of contaminated sediments through erosion processes (Dennis et al 2003;Macklin and Lewin 1989). Indeed, a number of studies have noted that the presence of contaminated floodplains can lead to the enrichment of contemporary fluvial sediments long after the cessation of mining activity (Leenaers 1989;Macklin and Klimek 1992;Owens et al 1999).…”
Section: Floodplain Sedimentmentioning
confidence: 97%
“…Their presence has implications for environmental health due to potential uptake by plants (Harding and Witton 1981;Jopony and Young 1993) and animals (Abrahams and Steigmajer 2003) and creates the possibility for the remobilization of contaminated sediments through erosion processes (Dennis et al 2003;Macklin and Lewin 1989). Indeed, a number of studies have noted that the presence of contaminated floodplains can lead to the enrichment of contemporary fluvial sediments long after the cessation of mining activity (Leenaers 1989;Macklin and Klimek 1992;Owens et al 1999).…”
Section: Floodplain Sedimentmentioning
confidence: 97%
“…In order to encourage tillering and normal sward formation, grass plants were cut down to the column rims with stainless steel scissors, leaving 1 cm of visible growth. The harvested plant material was discarded, as metal uptake by immature plants grown in pots may be atypical of that seen in subsequent harvests (Jopony and Young, 1993). Following the preliminary harvest, 20 mL of 0.02 M KNO 3 was added to the columns that contained the urban soils.…”
Section: Growth Room Bioassaymentioning
confidence: 99%
“…Sauvé et al (1998) examined the toxicological impact of (Cu 2+ ) and (Pb 2+ ) upon a variety of crop plants, soil organisms and soil microbial processes and found that the free metal ion activity explained toxic responses to a greater degree than the total soil metal concentration. Similarly, a number of studies have also focussed on metal concentration in the soil solution, [M soln ], as an indicator of intensity (Gerritse et al, 1983;Jopony and Young, 1993;Minnich et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…However, the extraction efficiency of the 0.01 mol CaCl 2 L − 1 is too low. EDTA normally extracts more Pb than plant uptake (Jopony and Young, 1993). Diluted HCl solution is often recommended for extracting heavy metals in acid soils.…”
Section: Introductionmentioning
confidence: 99%